2004
DOI: 10.1002/hbm.20035
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic distribution of serotonin transporters and receptor subtypes in human brain

Abstract: Several neurochemical in vitro and in vivo imaging studies have been aimed at characterizing the localization of serotonin receptors and transporters in the human brain. In this study, a detailed comparison of the distribution of a number of 5-HT receptor subtypes and the 5-HT transporter was carried out in vitro using human postmortem brain tissue. Anatomically adjacent whole hemisphere sections were incubated with specific radioligands for the 5-HT(1A), 5-HT(1B), 5-HT(2A), 5-HT(4) receptors and the 5-HT tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
195
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(222 citation statements)
references
References 59 publications
26
195
0
1
Order By: Relevance
“…The rACC has excitatory connections with the cACC that inhibits activation in the amygdala. It has been suggested that this loop is involved in fear extinction (eg Sotres-Bayon et al, 2006) and that especially the perigenual (supra-and subgenual parts combined) part of the ACC is strongly dependent on 5-HT metabolism (Varnas et al, 2004). Our findings of stronger amygdala activation going together with lower 5-HT availability are clearly compatible with the existence of such a loop.…”
Section: Discussionsupporting
confidence: 86%
“…The rACC has excitatory connections with the cACC that inhibits activation in the amygdala. It has been suggested that this loop is involved in fear extinction (eg Sotres-Bayon et al, 2006) and that especially the perigenual (supra-and subgenual parts combined) part of the ACC is strongly dependent on 5-HT metabolism (Varnas et al, 2004). Our findings of stronger amygdala activation going together with lower 5-HT availability are clearly compatible with the existence of such a loop.…”
Section: Discussionsupporting
confidence: 86%
“…Immunohistochemical studies reveal the presence of serotonin-1A (Aznar et al, 2003) and serotonin-2A (Jakab and Goldman-Rakic, 2000;Pazos et al, 1987b) receptors on nearly all CB-IR and PV-IR neurons. Moreover, serotonin-1A receptors are preferentially found in layer II of human prefrontal cortex (Burnet et al, 1995;Pazos et al, 1987a;Varnas et al, 2004) and PET studies show a significant reduction in radioligand binding to serotonin-1A receptors in depressed subjects (Bhagwagar et al, 2004a;Sargent et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the areas in which tryptophan depletion increased neural responses to emotional relative to neutral stimuli receive moderate-to-high densities of serotonergic projections from the dorsal and/or median raphe nuclei (Jacobs and Azmitia, 1992;Varnas et al, 2004). Multiple 5-HT receptor subtypes are present in each region, some of which when stimulated exert hyperpolarizing (ie inhibitory) effects on the neurons where they are expressed, and some of which exert depolarizing (ie excitatory) effects (Andrade, 1998;Peroutka et al, 1990).…”
Section: Discussionmentioning
confidence: 99%